2023
DOI: 10.1002/mp.16894
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of protoacoustics as a real‐time in‐line dosimetry tool for FLASH proton therapy

Kaitlyn Kim,
Prabodh Kumar Pandey,
Gilberto Gonzalez
et al.

Abstract: BackgroundApplying ultra‐high dose rates to radiation therapy, otherwise known as FLASH, has been shown to be just as effective while sparing more normal tissue compared to conventional radiation therapy. However, there is a need for a dosimeter that is able to detect such high instantaneous dose, particularly in vivo. To fulfill this need, protoacoustics is introduced, which is an in vivo range verification method with submillimeter accuracy.PurposeThe purpose of this work is to demonstrate the feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Based on the foregoing, simulation studies have already indicated the potential of RAI in capturing images of FLASH beams, applicable to both protons (Kim et al 2023) and electrons (Ba Sunbul et al 2021). Notably, recent experimental research has showcased the use of RAI with two linear arrays in an orthogonal setup for detecting the edges of FLASH electron beams up to 25 cGy, proving its feasibility (Oraiqat et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the foregoing, simulation studies have already indicated the potential of RAI in capturing images of FLASH beams, applicable to both protons (Kim et al 2023) and electrons (Ba Sunbul et al 2021). Notably, recent experimental research has showcased the use of RAI with two linear arrays in an orthogonal setup for detecting the edges of FLASH electron beams up to 25 cGy, proving its feasibility (Oraiqat et al 2020).…”
Section: Introductionmentioning
confidence: 99%